Parenteral pentazocine abuse leading to muscle abnormality: A case report (Indian Journal of Case Reports, 2016)
The injection of drug of abuse into muscle tissue leads to myositis, pain and ultimately fibrosis, atrophy and may be contracture of the specific muscle/s. Cases reporting the muscular side effects of intra venous (IV) drug abuse are few and this particular complication of drug abuse is not very well documented. We report a patient with myositis leading to atrophy of the shoulder muscles and following this the patient developed limitation of movements.